Таксономический статус, географическое распространение и внутривидовая структура комара-лимонииды дактилолабиса аберранс—Dactylotabis aberrans Sav. (Diptera, Linoniidae) - Савченко, Е.Н. (Вестник зоологии, 1969)
Dactylolabis aberrans Sav. (1963), which is distinguished as a new subgenus Coenolabis S a v., was found alongside with the Crimea in the Transcaucasia. In the Crimea and in the north of Transcaucasia it is represented by the nominal subspecies and in the south of Transcaucasia by the new subspecies: D.(C.) a. imereticus Sav. (Adjar-Imeretinsky ridge) and D.(C.) a. arsianensis Sav. (Arsiansky ridge). The types of new subspecies, differing from each other and from the nominal form by the structure of the IXth abdominal sternite, interbase and proctiger, are preserved in the collection of the Institute Zoology of the Academy of Sciences of the Ukrainian SSR (Kiev).